2005
DOI: 10.1183/09031936.04.00067204
|View full text |Cite
|
Sign up to set email alerts
|

Different lung responses to cigarette smoke in two strains of mice sensitive to oxidants

Abstract: The development of cigarette smoke-induced pulmonary changes in C57 Bl/6J and DBA/2 mice was investigated. Both strains are sensitive to oxidants and C57Bl/6J mice are moderately deficient in serum alpha1-proteinase inhibitor.Following chronic exposure to cigarette smoke, patchy emphysema was present in mice of both strains, but developed faster in DBA/2 mice. A positive reaction for mouse neutrophil elastase was seen on the septa of both strains. Additionally, the DBA/2 mice developed a uniform parenchymal di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
119
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(129 citation statements)
references
References 27 publications
8
119
0
2
Order By: Relevance
“…Consistent with previous observations (14,15), C57BL/6 WT mice displayed marked increases in lung airspace after 12-wk CS exposure relative to air-treated controls, as determined by comparative histologic examination (Fig. S1) and mean linear intercept (MLI) measurements (Fig.…”
Section: Resultssupporting
confidence: 76%
“…Consistent with previous observations (14,15), C57BL/6 WT mice displayed marked increases in lung airspace after 12-wk CS exposure relative to air-treated controls, as determined by comparative histologic examination (Fig. S1) and mean linear intercept (MLI) measurements (Fig.…”
Section: Resultssupporting
confidence: 76%
“…The clinical significance of our work is related to the finding of increased apoptosis of alveolar epithelial and endothelial cells in the lungs of COPD patients who smoke cigarettes and in animal models of emphysema (26,(30)(31)(32). Our data suggest that the effect of cigarette smoking on the A1AT antiapoptotic function is reversible and may be linked to the turnover of the protein as it is synthesized from the liver or to the restoration of native A1AT by reduction of the oxidized protein.…”
Section: Discussionmentioning
confidence: 79%
“…TNF-a R2 may be involved in the failure of weight gain in CS-exposed mice, since the current authors observed similar increases in weight in air-and CS-exposed TNF-a R2 KO mice, while a failure of weight gain was observed in WT and TNF-a R1 KO mice exposed to smoke. It is obvious that the smaller increases in weight in WT and TNF-a R1 KO mice were already visible in the first few weeks, while no emphysema has been observed following exposure to CS for 1 month (current authors' observations and [47]). In contrast to humans where weight loss, which occurrs in a subgroup of patients who develop severe COPD and emphysema, is a late phenomenon related to systemic effects of the disease, the early alterations of body weight in this mouse model of COPD seem to be due to an acute effect of cigarette smoking.…”
Section: Ai D'hulst Et Al Tnf-a R2 and Smoke-induced Emphysemamentioning
confidence: 91%